2013
DOI: 10.2166/ws.2013.130
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of hydraulically reversible and irreversible fouling species in ultrafiltration drinking water treatment systems using fluorescence EEM and LC–OCD measurements

Abstract: The application of the fluorescence excitation-emission matrix (EEM) approach and liquid chromatography–organic carbon detection (LC–OCD) analysis for the characterization of hydraulically reversible and irreversible fouling species, extracted from hollow fiber ultrafiltration (UF) membranes used in drinking water treatment, was demonstrated. Hydraulically reversible and irreversible fouling species were extracted from two pilot UF membrane systems operated in parallel with lake water as the feed. Two membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
3
6
0
Order By: Relevance
“…Consequently, there seems to be no need to apply any CEB under these filtration conditions, with the consequent lower reagent consumption and extension of membrane life. The higher detachment of BP by BW than other 10 organic fractions was in accordance with other studies [20,22]. Differences against other studies appear, however, in the percentage detachments.…”
Section: Removal Of Feed Water Constituentssupporting
confidence: 89%
See 3 more Smart Citations
“…Consequently, there seems to be no need to apply any CEB under these filtration conditions, with the consequent lower reagent consumption and extension of membrane life. The higher detachment of BP by BW than other 10 organic fractions was in accordance with other studies [20,22]. Differences against other studies appear, however, in the percentage detachments.…”
Section: Removal Of Feed Water Constituentssupporting
confidence: 89%
“…3 is in agreement with Peiris et al [20], who carried out UF of surface water under similar conditions (permeation duration of 30 min and BW duration of ca 2 min) and 30 reported recoveries of the initial permeability of <10% when BWs were applied and of 65-75% when chemical cleaning based on NaClO and citric acid in sequence was employed. In contrast, when treating surface water by UF (permeation duration of 30 min 35 and BW duration of 10 min), Wray et al [21] found that most of the total fouling observed (>70%) was hydraulically reversible.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…The eluted water after alkaline cleaning showed two fluorescence areas, region D (Ex/Em = 330/400 nm) and region C (Ex/Em = 240/400 nm). In contrast, the organics from acidic cleaning only had one fluorescence area (Ex/Em = 250/350 nm), which was marked as region F. As indicated in previous findings, region D is considered as a fluorescence response of the humic-like organics, while region C is believed to represent the hydrophobic and protein-like organics [46]. Although alkaline cleaning water had high concentrations of b a N-HPI organics (Fig.…”
Section: Analysis Following the Chemical Cleaning Of The Fouled Membrmentioning
confidence: 58%